School effectiveness and improvement practices in excellent schools in Malaysia and Brunei - A. Ghani, Muhammad Faizal; Siraj, Saedah; Mohd Radzi, Norfariza; Elham, Faisol (2011)
The Purpose of this research is to examine the school effectiveness and improvement practices in excellent schools in Malaysia and Brunei. Questionnaires based on the content of effective school model were distributed to the sample of 271 teachers from excellent schools in both countries in order to study on the practices of school effectiveness and improvement in their schools.This study will contribute to the existing body of knowledge on school effectiveness and improvement practices particularly experienced by Malaysia and Brunei. It also will benefit the school effectiveness practitioners in developing countries through academically systematic research findings.